Study of the relaxing effect of slow-dynamic gymnastic exercises - Angelov, V. (Journal of Applied Sports Sciences, 2019)
Introduction: The relaxation is a psychophysiological state of a person and in particular of athletes. On the basis of the literature sources, two main types of relaxation can be defined - physical and mental. Physical relaxation can be employed to reduce muscular tension and to improve coordination during the performance. It can be suggested that this psychophysiological state creates appropriate conditions for the development of flexibility, speed and all psychomotor qualities. That`s why an alternative new means with relaxing effect in this study will be investigated. Aim: The aim of the study is to prove that the slow-dynamic gymnastic exercises practice leads to reduction of muscular tension. According to the hypothesis of the research, the application of the mentioned exercises will increase the performers` sense of relaxation. The object of the study is a specialized set of gymnastic exercises which includes dynamic gymnastic exercises performed with slow movements and holding of static poses. Methods: The assessment of the relaxation degree was made through physiological and psychological parameters. The collected physiological data included heart rate, breathing frequency, blood pressure, and finger skin temperature measurement. The psychological data were assessed with Spielberger State Anxiety Inventory and four-point Likert type scale for self-rated relaxation. The measurements were made before and after the execution of the exercises. Results: Statistically significant changes were found for all variables studied, except systolic blood pressure. The comparison of the collected data from the two measurements showed the greatest differences in three indicators after the application of slow-dynamic gymnastic exercises - a decrease in the Spielberger Inventory results (-7.3 points, p<0.05), a decrease in the heart rate (-6 bpm, p<0.05) and an increase in the finger skin temperature of both hands (left: 3.5°, right: 3.8°, p<0.05). Conclusion: In conclusion, the established results confirm the hypothesis of the study and prove the relaxing effect of the slow-dynamic gymnastic exercises.